FAKTOR PENENTU MEMBAYAR ZAKAT DI BADAN AMIL ZAKAT NASIONAL (BAZNAS) DALAM KALANGAN PEMBAYAR ZAKAT DI KOTA MEDAN, INDONESIA: Determinants of Paying ZakÄh at the National ZakÄh Agency (BAZNAS) Among ZakÄh Payers in Kota Medan, Indonesia - Nasution, Eri Yanti; Ismail, Mohd Adib; Wahid, Hairunnizam (Jurnal Syariah, 2017)
Zakāh is an economic instrument that can improve the economy of a country. Indonesia is a country that has the largest Muslim population in the world. However, zakāh, which is the collective obligation of Muslims, has far from been implemented properly. Zakāh in Indonesia is still at the level of being a voluntary duty. This is exemplified by the fact that only some people pay zakāh fitrah. Their awareness to pay zakāh is still very low. This awareness is influenced by external and internal factors. The internal factor relates to a lack of chracter and knowledge, while the external factor regards the zakāh institution itself. Zakāh institutions are the most important factors to improve public awareness to pay zakāh. However, the issue which is being debated currently is about the inactive role of zakāh institutions towards improving the collection of zakāh. Many people have a lack of trust towards zakāh institutions which lead people to pay zakāh informally. This study will analyze the factors that determine why people pay zakāh to the National Zakat Agency (BAZNAS) in Medan, Indonesia. This study employed a survey method through questionaires to observe the determinants to pay zakāh. The data obtained was then analyzed using a descriptive method, Factor Analysis test, and Logistic Regression Analysis. The study found that people do not pay zakāh to BAZNAS because they are not aware that BAZNAS is the official zakāh institution. The factors that determine people’s awareness regarding the existence of BAZNAS should be the role of BAZNAS itself. This study is expected to help BAZNAS to improve their role in order towards increasing zakāh payment in Medan.